2011
DOI: 10.1111/j.1473-2165.2011.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

A 10% glycolic acid containing oil-in-water emulsion improves mild acne: a randomized double-blind placebo-controlled trial

Abstract: The 10% glycolic acid containing oil-in-water emulsion improved mild acne applied as monotherapy in this study significantly, already after 45 days of treatment. Regarding tolerability, there was no objective or subjective difference between the 10% glycolic acid containing oil-in-water emulsion and the corresponding placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 24 publications
(32 reference statements)
1
46
0
Order By: Relevance
“…Acidic detergents are favorable for maintaining a low SC pH . Moreover, mild acne is significantly improved after application of an acidic leave‐on product with pH 4 …”
Section: Ph and Antimicrobial Effectsmentioning
confidence: 99%
“…Acidic detergents are favorable for maintaining a low SC pH . Moreover, mild acne is significantly improved after application of an acidic leave‐on product with pH 4 …”
Section: Ph and Antimicrobial Effectsmentioning
confidence: 99%
“…However, several studies (including a large multicentre, double‐blind, randomized, vehicle‐controlled trial) have demonstrated the safety and efficacy of a preparation containing a combination of the AHA glycolic acid and retinaldehyde (a form of vitamin A) in treating acne and post‐inflammatory hyperpigmentation associated with acne . Furthermore, a recent single‐centre, double‐blind, randomized, placebo‐controlled trial on 10% glycolic acid monotherapy for mild acne showed significant improvement in acne compared with the placebo after 90 days of treatment …”
Section: Alpha‐hydroxy Acidsmentioning
confidence: 99%
“…). The chemical peeling agents were as follows: salicylic acid 20–30%, glycolic acid 10–70%, Jessner solution, trichloroacetic acid (TCA) 25%, mandelic acid 10%, amino fruit acid 20–60% and lipo‐hydroxy acids 0.3–10% . The majority of the studies ( N = 8/11) compared two peeling agents to each other .…”
Section: Resultsmentioning
confidence: 99%
“…Strong evidence of efficacy was found on behalf of glycolic acid (10% and 40%). This was due to two randomized, double‐blinded, placebo‐controlled studies with high methodological quality . One study investigated the efficacy of lipo‐hydroxy acid (0.3%) compared to benzoyl peroxide, demonstrating no statistically significant results between the lipo‐hydroxy acid‐group and the benzoyl peroxide‐group.…”
Section: Resultsmentioning
confidence: 99%